The role of media in influencing students' STEM career interest - Chen Chen; Stephanie Hardjo; Gerhard Sonnert; Jiaojiao Hui; Philip M. Sadler (SpringerOpen, 2023)
Abstract Background Digital media are pervasive in the lives of young people and provide opportunities for them to learn about STEM. Multiple theories argue that the STEM media environment may shape how youth see a STEM career in their future. Yet, little is known about how pre-college digital media consumption may be related to students' STEM career interest at the beginning of college. The wide variety of STEM media also raises the question of potentially different effects and pathways by media type. In this study, we collected a nationally representative sample of more than 15,000 students in their first year in U.S. colleges and universities. We asked about their career interests at the beginning of college and also asked them to retrospectively report their STEM media consumption during high school. Results We found that watching STEM-related TV and online videos, as well as playing STEM-related video games during high school, were positively associated with students' STEM career interests at the beginning of college. However, we also found that STEM media consumption did not impact directly on STEM career interest, but acted through two intermediaries: STEM identity (I and others see me as a STEM person) and three personal career outcome expectations: a high interest in self-development (enhancement and use of talents), and low interests in material status (money, fame, power) and in interpersonal relationships (helping, and working with, other people). Conclusions This study finds that STEM media have a significant effect in fostering STEM career interest, with most of the effect coming from STEM TV, STEM video viewing, and STEM video games. The effect is mediated mainly through students' identity and, to a lesser extent, through personal values, such as self-development, material, and interpersonal relationship values. This study suggests that media communication should be mindful of how different platforms may deliver nuanced and varied messages of what STEM careers may afford and who can succeed in STEM.